2022
DOI: 10.3389/fpsyt.2022.871754
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between 5-Hydroxytryptamine and Its Metabolite Changes With Post-stroke Depression

Abstract: Post-stroke depression (PSD) is the most common and serious sequelae of stroke. Approximately 33% of stroke survivors were affected by PSD. However, many issues (e.g., incidence, diagnostic marker, and risk factor) related to PSD remained unclear. The “monoamine hypothesis” is a significant hypothesis for depression, which suggests that three monoamines play a key role in depression. Therefore, most current antidepressants are developed to modulate the monoamines on PSD treatment, and these antidepressants hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 200 publications
0
14
0
Order By: Relevance
“…Disgust is the least studied basic emotions; recently, a growing number of studies suggest that disgust plays a significant role in our lives and in many psychological disorders [ 35 , 36 ]. Many experiments have confirmed the reward function of DA and the mood arousal function of NE, but the relationship between serotonin (5-HT) and depression is much more important, for most current antidepressants are targeting 5-HT [ 37 , 38 , 39 ].…”
Section: Monoamine Neurotransmitters Mediate Three Core Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disgust is the least studied basic emotions; recently, a growing number of studies suggest that disgust plays a significant role in our lives and in many psychological disorders [ 35 , 36 ]. Many experiments have confirmed the reward function of DA and the mood arousal function of NE, but the relationship between serotonin (5-HT) and depression is much more important, for most current antidepressants are targeting 5-HT [ 37 , 38 , 39 ].…”
Section: Monoamine Neurotransmitters Mediate Three Core Effectsmentioning
confidence: 99%
“…The pathogenesis of pre-perimenopausal depression is also suggested to be related to reduced levels of estrogen (estradiol, E2), and E2 replacement therapy has been used to treat perimenopausal depression [ 130 ]. However, recent studies have found that E2 has little effect on perimenopausal depression; instead, estrogen deficiency-induced female depression might be related to 5-hydroxytriptamine (5-HT) deficiency [ 36 ]. In addition, luteinizing hormone (LH) is significantly altered during the menstrual cycle, perinatal, and perimenopausal periods, which may be the main cause of depression [ 131 ].…”
Section: Monoamines and Neuroendocrinementioning
confidence: 99%
“…Previously, we originally proposed the “Three Primary Color Model of Basic Emotions”, trying to differentiate the functions of these three monoamines. We hypothesized that the three monoamines work differently to make three distinct emotions, as in the three primary colors [ 74 , 75 ]. Here, we further propose that their effects in treating MDD are also different in that catecholamine can directly induce emotional arousal, while 5-HT can induce sedation and sleep.…”
Section: Monoamines and The Glymphatic Systemmentioning
confidence: 99%
“…Monoamine neurotransmitters are perfectly suited to the regulation of mitochondria in the brain, and enhancing the energy supply function, and mitochondria have recently been found to play a pivotal role in emotional arousal. Emotion arousal can induce NE release in the locus coeruleus and also in other monoamine neurotransmitters [ 75 ]. However, a side-effect of monoamine release is enhancing neural activity through the parallel activation of both neuronal mitochondria and astrocytic clearance to establish a synergistic mechanism of antagonizing ROS-induced oxidative stress and inflammation.…”
Section: Monoamines and The Glymphatic Systemmentioning
confidence: 99%
“…Due to changes in their body, they cannot get over their symptoms on their own [7]. Another study demonstrated that due to damage of nerve cells, chances of brain hemorrhage increased multiple times [8,9]. Depression doesn't only effect brain, it weakens heart, immune system and musculoskeletal system Late life depression showed more harmful effects as compared to early life depression.…”
Section: Introductionmentioning
confidence: 99%